Disseminated Mycobacterium chimaera Presenting as Vertebral Osteomyelitis - Daphne M. Moutsoglou; Frank Merritt; Ethan Cumbler (Case Reports in Infectious Diseases)
Mycobacterium chimaera, a member of the Mycobacterium avium complex, is a slow-growing, nontuberculous mycobacterium associated with outbreaks in cardiac-surgery patients supported on heart-lung machines. We report a case of an elderly woman on chronic prednisone who presented with a six-month history of worsening chronic back pain, recurrent low-grade fevers, and weight loss. Imaging identified multilevel vertebral osteomyelitis and lumbar soft-tissue abscess. Abscess culture identified M. chimaera.